Supporting self-regulated teaching.: Designing a digital app to support data-based decision-making - Alvarez, Lionel; Cuko, Kostanca; Boéchat-Heer, Stéphanie; Coen, Pierre-François (Swiss Journal of Educational Research, 2021)
A university teacher who wishes to regulate his or her professional practices to meet the needs of learners is sometimes lacking information to identify the actions to be taken. In order to enable him or her to go beyond his or her own feelings and impressions, two Universities of Teacher Education in the French-speaking part of Switzerland have developed a digital tool called OURA, which aims to support the regulation of teaching/learning activities at the university level. This article explains the theoretical foundations that underpin its development: firstly, the data-based decision-making and the teaching analytics, and secondly, the theoretical foundations of the various fields and dimensions taken into account in the tool.